Protein S Deficiency - An Uncommon Cause with Common Presentation - Kora, Nabanita; Das, Rajib; Som, Sabyasachi; Laha, Sumanta; Bannerji, Nayan; Rana, Kriti S (Journal of Nepal Paediatric Society, 2016)
Correction: The correct PDF for this article was loaded on 9th March 2017. We offer our sincere apologies for having the wrong PDF loaded for this article. Stroke in child poses a major health problem. Thrombophilic factors have been implicated in 4-8% of young stroke worldwide. Protein S deficiency is a very rare cause of stroke. A few cases have been reported in literature. We are reporting a rare case of protein S deficiency causing stroke in a two year old child. J Nepal Paediatr Soc 2015;35(2):192-194